Use of the Brief Shame and Guilt Questionnaire in Deaf and Hard of Hearing Children and Adolescents - Broekhof, Evelien (Assessment, 2017)
No assessment tools are available to measure shame and guilt in children who are deaf or hard of hearing (DHH), while these self-conscious emotions might play a role in the frequently noted social and behavioral problems in this group. Therefore, the aim of this study was to validate the Brief Shame and Guilt Questionnaire (BSGQ) in DHH children. In addition, we examined associations of shame and guilt with social anxiety, self-esteem, delinquency, and psychopathic behaviors. A sum of 225 hearing (M(age) = 11.62 years) and 108 DHH (M(age) = 11.82 years) participants completed the self-report BSGQ. Multigroup confirmatory factor analysis confirmed the two-factor structure (i.e., shame and guilt) of the BSGQ in the DHH group. Measurement invariance was established across both groups. However, the DHH group reported lower levels of self-conscious emotions in comparison with the hearing group. The BSGQ showed good concurrent validity, where shame was associated with higher levels of social anxiety and lower levels of self-esteem, and guilt was associated with lower levels of delinquency and psychopathic behavior in both groups. Future research should investigate the potential behavioral consequences of lower reported levels of self-conscious emotions in DHH youth.